Evolving Dynamics of Corporate Social Responsibility: A Comparative Analysis of Global Practices - Payoj Raj Singh, Poonam, Vinod Kumar (Journal of Informatics Education and Research, 2024)
Over the years CSR has evolved to be an important factor in business management across the globe as firms embraced so-called responsible capitalism as a way of doing business. This paper aims at discussing the changes in the concept and practices of CSR by providing the comparison of developed and developing nations. CSR activities are shaped by legal requirements, public pressure, and economic conditions, all of which are analysed in the paper. In this deliverable, which is the manuscript of the paper, the empirical analysis compares 100 companies from diverse world regions for the evaluation of two hypotheses that concern the structure and the levels of transparency of CSR practices and the role of external factors in these practices. The research shows that various industries have different CSR strategies and stresses on the role of the regulation and social environment in these activities.